Virtual reality-based evaluation of indoor earthquake safety actions for occupants. (August 2021) - Zhang, Furong; Xu, Zhen; Yang, Yajun; Qi, Mingzhu; Zhang, Huazhen
Abstract: Evaluations of indoor earthquake safety actions can provide effective guidance for occupants, and can be beneficial for reducing earthquake-induced casualties. Accordingly, in this study, a virtual reality (VR)-based evaluation method is proposed for indoor earthquake safety actions. Specifically, an indoor seismic damage scene is constructed based on the Federal Emergency Management Agency (FEMA) P-58 method and a physics engine, by which the damage and movements of indoor nonstructural components can be accurately calculated. Subsequently, a virtual body model is created, and a corresponding inverse kinematics (IK) algorithm is developed to accurately track the earthquake safety actions of occupants. Finally, a human safety model based on collision kinetic energy and fatal conditions is designed for quantitatively evaluating the effectiveness of earthquake safety actions. Taking an office room and living room as case studies, three earthquake safety actions (i.e., "drop, cover, and hold on, " "triangle of life, " and "run outside") are evaluated using the proposed method. The results indicate that "drop, cover, and hold on" is the safest action in most earthquake scenarios. The outcomes of this study can be used to rate the effectiveness of various earthquake safety actions, and to support occupant safety decision-making.